The 1986 Tile Competition: a Culinary Institute, Plazza d'Italia, New Orleans - Joseph Biondo; Matt Knox; John Low; Tan Tee Hung (Oz, 1987)
The project selected for the Fall 1986 Tile Competition was a culinary institute for 100 students located on a site adjacent to the Piazza d 'Italia in New Orleans. The plaza, completed in the late 1970s, was a design collaboration between Charles Moore and Perez Architects.